CORRELATION BETWEEN MATERNAL BEHAVIOR AND CHILDHOOD DENTAL CARIES (Proceedings OPTIMAL, 2025)
Early Childhood Caries (ECC) remains the most prevalent disease among children. The role of mothers plays a critical part in forming their children’s dental hygiene practices, which influences the incidence of dental caries. This study aims to analyze the correlation between maternal behavior and the occurrence of ECC. This study employed a cross-sectional design involving 305 mothers of children from seven kindergartens. Data on maternal behavior were collected using a structured questionnaire, while children’s dental status was assessed through clinical examination based on the DMF (Decayed, Missing, and Filled) index. Statistical analyses included descriptive statistics, normality testing, and correlation analysis using the ANOVA test with a significance level of α = 0.05. The mean maternal behavior score was 43.134 (SD = 6.807), and the mean DMF index of children was 7.345 (SD = 4.609). The normality test showed that maternal behavior was not normally distributed (p < 0.0001), whereas the DMF variable was normally distributed (p = 0.147). The correlation test revealed a very weak and non-significant relationship between maternal behavior and children’s dental caries status (r = –0.067, p = 0.306). There was no significant correlation between maternal behavior and the incidence of dental caries in children. These findings indicate that maternal behavior alone may not directly influence children’s oral health outcomes. Future interventions should adopt a multifactorial approach that includes improving maternal oral health literacy, dietary supervision, and access to dental care services.